Inhibitory effect of AK-7 mediates by apoptosis, increases DNA fragmentation and caspase-3 activity in human glioblastoma multiforme cells (Bangladesh Journal of Pharmacology, 2022)
Sirtuins (SIRTs) which are nicotinamide adenine dinucleotide (NAD+) dependent class III histondeacetylases have a controversial role in cancer. In this study, the effect of pharmacological inhibition of AK-7, a SIRT2 inhibitor, was investigated in U87 glioblastoma multiforme cells. The cytotoxic effect of AK-7 was evaluated by XTT analysis. After AK-7 treatment, colony forming capacity of cells was determined and apoptosis was evaluated. The expression levels of apoptosis-related genes were determined by qRT-PCR. According to the results, AK-7 inhibited cell proliferation in a dose- and time-dependent manner. After AK-7 treatment, the colony forming capacity of U87 cells was suppressed. And, AK-7 increased apoptosis rate, DNA fragmentation, and caspase-3 activity. According to qRT-PCR, a significant increase was observed in expression levels of apoptosis-related genes. This study revealed that AK-7 inhibits cell proliferation and induces apoptosis in glioblastoma multiforme cells and SIRT2 inhibition can be evaluated as a therapeutic approach in glioblastoma multiforme.